Harvesting Water‐Evaporation‐Induced Electricity Based on Liquid–Solid Triboelectric Nanogenerator. Issue 17 (17th April 2022) - Chi, Jingu; Liu, Chaoran; Che, Lufeng; Li, Dujuan; Fan, Kai; Li, Qing; Yang, Weihuang; Dong, Linxi; Wang, Gaofeng; Wang, Zhong Lin
Abstract: Harvesting energy from natural water evaporation has been proposed as a promising alternative to supply power for self‐powered and low‐power devices and systems, owing to its spontaneous, ubiquitous, and sustainability. Herein, an approach is presented for harvesting water‐evaporation‐induced electricity based on liquid–solid triboelectric nanogenerators (LS‐TENGs), which has various advantages of easy preparation, substrate needless, and robustness. This developed harvester with porous Al2 O3 ceramic sheet can generate a continuous and stable direct current of ≈0.3 µA and voltage of ≈0.7 V by optimizing the sheet physical dimensions and ambient parameters such as relative humidity, temperature, wind velocity, and ion concentration. The output power also can be improved significantly by series or parallel connection the harvesters, which has superior electrical compatibility and environmental suitability. The development of the water‐evaporation‐induced electricity harvesting shows many application prospects including power supply for digital calculator and charging capacitor. This research provides an in‐depth experimental study on water‐evaporation‐induced electricity harvesting based on LS‐TENGs and an efficient approach to supply electricity for low‐power devices. Abstract : A liquid–solid triboelectric nanogenerator (LS‐TENG) based on a porous Al2 O3 sheet is developed for harvesting water‐evaporation‐induced electricity. The optimized LS‐TENG achieves sustainable stable output direct current ≈0.3 µA and voltage ≈0.7 V. The output electricity can be multiplied to power digital calculators or charge capacitors by connecting the LS‐TENGs in series or parallel.